Assessing the Effect of Air Ventilation on the Dispersion of Exhaled Aerosol Particles in a Lecture Hall: Simulation Strategy and Streamlined Workflow - Arnav Ajmani; Lars Kirchhof; Alireza Rouhi; Carsten Mehring (Fluids)
An efficient solution strategy based on fluid network modeling, computational fluid dynamics (CFD) and discrete particle modeling (DPM) is presented in order to predict and improve air quality, specifically regarding breathing aerosol concentration, in a person-occupied mechanically ventilated room. The efficiency of the proposed workflow is evaluated for the specific case of a lecture hall. It is found that the actual vent system is imbalanced and inefficient in managing the aerosol concentration within the room. Despite a high volumetric exchange rate, aerosol residence times and local aerosol concentrations remain high over an extended period of time, without additional efforts to alter air flow circulation throughout the room. The proposed strategy illustrates how such changes can be efficiently implemented in the basic 1D/3D co-simulation workflow. Analysis of the lecture hall and vent system shows that the execution time for the overall process workflow can be optimized by the following: (1) CAD geometry generation of the room via 3D laser scanning, (2) mesh generation based on the anticipated air discharge behavior from the vent system and (3) by employing HPC resources. Additional simplifications such as the decoupling of vent air flow and room aerodynamics, as observed for the investigated test case, one-way coupling between air flow and aerosol dispersion at low aerosol concentrations and the successive solution of flow field equations can further reduce the problem’s complexity and processing times.